1981
DOI: 10.1111/j.1471-4159.1981.tb01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Changes of Amino Compounds in Human and Rat Brain

Abstract: Contents of 35 amino acids and related compounds were measured in whole rat brain, and in superficial areas of biopsied and autopsied human brain, after incubation for various intervals at temperatures simulating those likely to occur in cadavers under mortuary conditions. These data should aid interpretation of values for amino compounds determined in autopsied brain from patients with neurological or psychiatric disorders. The contents of glutamic acid, glutamine, taurine, phosphoethanolamine, cystathionine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
94
2

Year Published

1981
1981
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(111 citation statements)
references
References 21 publications
15
94
2
Order By: Relevance
“…Ifthe mean of the measurements on the control subject studied multiple times is included as a single value, the group mean and standard deviation are unchanged (mean, 1.1 ,umol/cm3 of brain, SD, 0.1). The 'H 0 6 2 4 Vigabatrin, g/day NMR measurement is in good agreement with reported measurements of GABA concentration in biopsied temporal and frontal lobes, which ranged from 0.5 to 1.4 ,umol/cm3 of brain (47,(51)(52)(53) when delays between tissue excision and freezing were kept to a minimum. Serial 'H NMR measurements in a single patient ranged from 0.7 ,umol/cm3 of brain before vigabatrin was started to 2.9 on a dose of 4 g per day.…”
Section: Methodssupporting
confidence: 88%
“…Ifthe mean of the measurements on the control subject studied multiple times is included as a single value, the group mean and standard deviation are unchanged (mean, 1.1 ,umol/cm3 of brain, SD, 0.1). The 'H 0 6 2 4 Vigabatrin, g/day NMR measurement is in good agreement with reported measurements of GABA concentration in biopsied temporal and frontal lobes, which ranged from 0.5 to 1.4 ,umol/cm3 of brain (47,(51)(52)(53) when delays between tissue excision and freezing were kept to a minimum. Serial 'H NMR measurements in a single patient ranged from 0.7 ,umol/cm3 of brain before vigabatrin was started to 2.9 on a dose of 4 g per day.…”
Section: Methodssupporting
confidence: 88%
“…Taurine concentrations have been shown to remain stable for up to 8 h in postmortem human brain (Perry et al, 1981), and we have also recently shown taurine to remain stable in human brain tumour biopsies (AS2 and GBM) and normal rat brain during prolonged HRMAS spinning (Opstad et al, 2008c). Thus, significant postischaemic changes in tumour biopsy taurine concentrations as a result of the biopsy excision, and/or the HRMAS procedure appear unlikely.…”
Section: Discussionmentioning
confidence: 96%
“…This effect, however, was not shared by all brain regions, as serotonin levels remained stable over an 18-h postmortem interval in the cingulate cortex (25). Furthermore, concentrations of many metabolites, such as myo-inositol, creatine, glutamine, glutamate, N-acetylaspartate, and taurine were shown to remain stable in the postmortem brain tissue over long time intervals (22,23,26,27). Similarly, experiments quantifying brain polyamines, such as spermine, spermidine, and putrescine, in postmortem human brain using GC-MS did not report any significant relationship between these metabolite concentrations and postmortem interval (28).…”
Section: Freely Available Online Through the Pnas Open Access Optionmentioning
confidence: 91%
“…Previous studies that have used proton magnetic resonance spectroscopy in human and rat brain biopsy samples have shown that concentrations of metabolites associated with anaerobic glycolysis, such as glucose, alanine, glutathione and lactate, change after death (21)(22)(23)(24). In rat brain, postmortem delay also leads to concentration changes of dopamine, norepinephrine, and serotonin in the occipital cortex.…”
Section: Freely Available Online Through the Pnas Open Access Optionmentioning
confidence: 99%